PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PUSAT STATISTIK ACEH - Dimas Bagus Susanto; Maulidar Maulidar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of organizational commitment on employee performance at the Aceh Statistics Center. To determine the effect of job satisfaction on employee performance at the Aceh Statistic Center Office. To determine the mutual influence between organizational commitment and job satisfaction on employee performance at the Aceh Statistics Center. While the object of this research is organizational commitment and job satisfaction and employee performance with a total of 70 respondents. The results showed that organizational commitment and job satisfaction had a significant effect on employee performance at the Central Bureau of Statistics. Multicollinearity Test Results VIF value of 1.008 which means <10, thus it can be concluded that there is no multicollinearity. Test Results - Heteroscedasticity by looking at the distribution of random points both above and below the number 0 on the Y axis, it can be concluded that there is no heteroscedasticity in this regression model. The results of the Normality Test show that the normal graph pattern shows the distribution of points around the diagonal line, and following the direction of the diagonal line indicates that the regression model meets the assumptions of normality. After conducting research at the Aceh Central Statistics Agency, it is hoped that the Central Statistics Agency office will continue to improve performance and service to the community and to all employees to be able to continue to improve performance, so that the results obtained will be better.